2021
DOI: 10.21037/cdt-21-110
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA XIST serves as a diagnostic biomarker in gestational diabetes mellitus and its regulatory effect on trophoblast cell via miR-497-5p/FOXO1 axis

Abstract: Background: Gestational diabetes mellitus (GDM) is increasingly common in pregnancy. This study's purpose was to identify the expression of XIST and manifest the potential mechanism of XIST in GDM.Methods: Ninety-three patients with GDM and 93 normal pregnant women were included in this investigation. qRT-PCR was conducted to evaluate the expression of miR-497-5p and XIST and the relationship between XIST and fasting blood glucose (FBG) was explored by Pearson assay. The clinical diagnosis of XIST on GDM patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Our research exhibited that the lncRNA XIST was expressed in abundance in the plasma of DVT patients compared with the plasma of normal people. There were similar reports in other cardiovascular diseases related to DVT [9][10][11]. In addition, we found that lncRNA XIST knockdown could increase cell viability and reduce apoptosis and ameliorate the change of TF level in HUVECs induced by IL-1β.…”
Section: Discussionsupporting
confidence: 87%
“…Our research exhibited that the lncRNA XIST was expressed in abundance in the plasma of DVT patients compared with the plasma of normal people. There were similar reports in other cardiovascular diseases related to DVT [9][10][11]. In addition, we found that lncRNA XIST knockdown could increase cell viability and reduce apoptosis and ameliorate the change of TF level in HUVECs induced by IL-1β.…”
Section: Discussionsupporting
confidence: 87%
“…The protein PSMB8 was observed in the proteosome that is responsible for ATP-dependent protein degradation, which is a direct reason for developing T2D [ 60 ]. Patients with T2D had a higher level of XIST expression than those without diabetes [ 61 ]. Type 2 diabetes risk is substantially increased by DUSP8 expression in individuals [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further research has shown that diabetes is partly attributed to cell damage, namely, apoptosis of the islet β cells. The inflammatory and anti-inflammatory factors released by islet cells include IL-1 and IL-10, and the imbalance of these inflammatory and anti-inflammatory factors secreted may cause islet β-cell damage and lead to its death ( Li et al, 2021c ; Li et al, 2021a ; Tanwar et al, 2021 ). Functionally, insulin promotes glucose uptake and glycogen synthesis, and the glycogen synthesis is a further factor affecting the absorption and metabolism of blood sugar, which increases insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%